Leadership and challenges in covid 19 pandemonium - Akbariansyah Akbariansyah; Rina Septina; Bayu Iswana (Journal of Educational and Learning Studies, 2021)
For Indonesia, the COVID-19 virus is a challenge with very high complexity, thus it requires quality leadership and is able to face the complexities of leadership that is able to deal with situations like today. Currently the government has made a policy in the form of PSBB as a solution to limit and suppress the transmission of COVID-19, so consistency is needed both in its implementation. Without consistency, the implementation of the bureaucracy will be chaotic without direction, and can reduce public confidence in the government. There is an implied meaning that the leader is not born biologically but ideologically forged. Therefore, a leader develops and is formed from a socio-cultural background in a society. In another way, environmental conditions that can directly shape the character of leadership in a society. The more complex a social life system is, the more leadership is needed to adapt and to overcome the complex challenges.